Characterization and comparative evaluation of wound healing potential of Ajugarin I and Ajuga bracteosa Wall. ex Benth - Wasti, Yusra; Muntaqua, Durdana; Majid, Muhammad; Naz, Iffat; Zafar, Aroosa; Khan, Safir Ullah; Kazmi, Syeda Tayyaba Batool; Rehman, Tofeeq Ur; Irshad, Nadeem; Fatima, Humaira (Frontiers in Chemistry, 2024)
Ajuga bracteosa (family: Lamiaceae), commonly known as kauri booti, is an important ethnomedicinal plant. The current research was conducted to appraise and compare the in vitro antioxidant and antibacterial profiles as well as in vivo wound healing potentials of Ajugarin I and A. bracteosa extract. Ajugarin I and polyphenols in A. bracteosa were enumerated by reversed-phase high-performance liquid chromatography analysis that confirmed significant amounts of Ajugarin I (2.2 ± 0.02 μg/mg DW) and other phenolic compounds (14 out of 17 standards). A. bracteosa (374.4 ± 0.20 µg AAE/mg of DW, 201.9 ± 0.20 µg AAE/mg of DW, 87 ± 0.30%) showed a higher antioxidant profile compared to Ajugarin I (221.8 ± 0.50 µg AAE/mg of DW, 51.8 ± 0.40 µg AAE/mg of DW, 27.65 ± 0.80%) with 1.86-, 3.89-, and 3.15-fold greater activity in ferric reducing antioxidant power, total antioxidant capacity, and free radical scavenging assays, respectively. Likewise, A. bracteosa showed antibacterial activity against 3/5 strains (MIC 25–200 μg/ml) than Ajugarin I (2/5 strains; MIC 50–200 μg/ml). Hemolytic (<2% hemolysis) and dermal toxicity tests rendered both samples non-toxic. Additionally, A. bracteosa (100 ± 2.34% at day 12; 9.33 ± 0.47 days) demonstrated 1.11- and 1.24-fold higher percent wound contraction and epithelization time, respectively, than Ajugarin I (95.6 ± 1.52% at day 12; 11.6 ± 0.47 days) as assessed by an excision wound model in mice. Histopathological examination further reinforced the better wound healing potential of A. bracteosa with good epithelization, collagen synthesis, fibroblast proliferation, and revascularization. Briefly, we endorse the significant comparative antioxidant, antibacterial, and wound healing activities of A. bracteosa and Ajugarin I and present these as prospective candidates for wound healing drugs.